IMPLEMENTASI PROGRAM LAYANAN ANANDA SEHAT DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SUKABUMI - Arif, Samsul; Dian Purwanti; Tuah Nur (Kebijakan : Jurnal Ilmu Administrasi, 2024)
The Children’s Birth Certificate Service through Online Immediately, Easily and Quickly or called Ananda Sehat Service is a form of online service operated by means of an application with the purpose of making the community easier, faster and happier for obtaining birth certificate. The research was aimed at finding out the implementation of the Ananda Sehat Service program at the Population and Civil Registration Department of Sukabumi City. The research method used was descriptive qualitative. The techniques of collecting data conducted included observation, interview and documentation. The research applied the three dimensions of program implementation from Charles O Jones. The results indicate that the implementation of the Ananda Sehat Service program at the Population and Civil Registration Department of Sukabumi City is considered to be still less optimal because the application of Ananda Sehat Service often experiences bugs during accessing its services; the information about the existence of Ananda Sehat Service has not evenly been distributed to the society; and, there is no clarity regarding Standard Operating Procedures and schedule for system maintenance of the Ananda Sehat Service.